Determinants of Teacher Satisfaction: A Study of School Policies, Resource Allocation, and Managerial Support - Astuti, Dea Dri; Suryaputra, Ronald; Kibtiyah, Asriana (Jurnal Paedagogy, 2025)
This study aims to analyze the influence of school policies, resource allocation, and managerial support on teacher satisfaction. Using a quantitative approach, the study employed a survey method and applied Structural Equation Modeling with Partial Least Squares (SEM-PLS) using SmartPLS 4 software. A census sampling technique was used, in which all 63 teachers at SMAN 3 Rembang were included as respondents, representing the entire population. The results show that: (1) school policies have a positive and significant influence on teacher satisfaction; (2) resource allocation has a positive and significant influence on teacher satisfaction; (3) managerial support has a positive and significant influence on teacher satisfaction; and (4) school policies, resource allocation, and managerial support simultaneously have a positive and significant influence on teacher satisfaction. These findings suggest that well-managed schools, in terms of structure and administration, can enhance teachers’ satisfaction, enthusiasm, and commitment to both their institution and their profession.